Using Tests of Controls in the Audit Practice - Lubenchenko, О. Е.; Redko, О. Yu. (Statistics of Ukraine, 2021)
Selected problems related with obtaining audit evidence through making tests of controls are discussed. It is demonstrated that the internal economic control is an obligatory type of control that covers the processes of information flows and processing, delegation of authorities and sharing of responsibilities, performance assessment at unit and company level, physical protection of assets. In time of the audit, the management of an auditing firm needs to have understanding of controls exercised by its client, laying grounds for assessing the risk of essential distortions of financial reports and for elaborating further auditing procedures required for obtaining relevant audit evidence. The working document “Questionnaire on Internal Control”, elaborated by the author, contains information on controls obtained from management staff of a client by all the essential items of financial reports. When an auditor takes decision to rely on the results of internal control on certain areas of activities, these areas need to be checked through collecting sufficient audit evidence of the operational efficiency of the respective tools of control in certain circumstances. Tests of controls allow minimizing the time for auditing procedures in response to the risks assessed by an auditor. The elaborated working documents “Test of Controls: Stocks” and “Test of Controls ‘Inventory Monitoring’” allow to assess the probability of distortions of financial reports at item level due to mistakes or fraudulent activities of stakeholders, the impact of auditing procedures and collected audit evidence on the formation of the auditor’s opinion, and to create feedbacks between task force members and management of a company whose reporting is audited. When an auditor is not satisfied with the performance of the client’s internal audit, he/she will launch substantive procedures, analytical and alternative procedures, thus increasing the scope of the audit sample.